Distribution of selenium and zinc in soil-crop system and their relationship with environmental factors. (March 2020) - Xu, Yuefeng; Hao, Zhe; Li, Yonghua; Li, Hairong; Wang, Li; Zang, Zhenfeng; Liao, Xiaoyong; Zhang, Ru
Abstract: Selenium (Se) and zinc (Zn) are essential microelements for humans with crucial biological functions. In this study, we determined Se and Zn concentrations in soils and rice grains on Hainan Island and investigated how their spatial distributions are related to soil mineral elements, topography, and vegetation coverage. Overall, the concentrations of Se and Zn in soils were higher than the background values for Chinese soil; the Se concentrations in rice grains were higher than the threshold value for Se deficiency in grains, but Zn concentrations were lower than the proposed critical concentration. Both Spearman's correlation and stepwise regression analysis showed that the concentrations of soil Fe and Ca significantly affected soil Se and Zn: a difference of 1 g kg −1 in soil Fe changed soil Se by 2.820 μg kg −1 and soil Zn by 0.785 mg kg −1, respectively, while a difference of 1 g kg −1 in soil Ca changed soil Se by 3.249 μg kg −1 and soil Zn by 0.356 mg kg −1, respectively. For rice grains, Se and Zn concentrations decreased with increasing elevation; every 100 m increase in elevation could decrease Se by 0.022 mg kg −1 and Zn by 0.912 mg kg −1 . Moreover, the impact of Fe and Ca on soil Zn was relatively strong in the northeast region, while the influence of elevation on rice grain Se was more significant in the central region. The findings contribute to a better understanding of factors driving the distribution of Se and Zn in soils and crops. Graphical abstract: Image 10175 Highlights: Effect of soil chemistry, topography and vegetation on soil–rice Se/Zn was studied. Hainan rice grains were relatively high in Se but low in Zn. Soil mineral composition had a significant impact on Se and Zn contents in soils. Soil-Fe difference of 1 g kg −1 changed soil Se by 2.820 μg kg −1 and Zn by 0.785 mg kg −1 . Se and Zn contents in rice grains decreased with increasing elevation.